Unraveling retrograde signaling pathways: finding candidate signaling molecules via metabolomics and systems biology driven approaches - Caldana, Camila; Fernie, Alisdair R.; Willmitzer, Lothar; Steinhauser, Dirk (Frontiers in Plant Science, 2012)
A tight coordination of biological processes between cellular compartments and organelles is crucial for the survival of any eukaryotic organism. According to cellular requirements, signals can be generated within organelles, such as chloroplasts and mitochondria, modulating the nuclear gene expression in a process called retrograde signalling. Whilst many research efforts have been focused on dissecting retrograde signalling pathways using biochemical and genetics approaches, metabolomics and systems biology driven studies have illustrated their great potential for hypotheses generation and for dissecting signalling networks in a rather unbiased or untargeted fashion. Recently, integrative genomics approaches, in which correlation analysis has been applied on transcript and metabolite profiling data of Arabidopsis thaliana, revealed the identification of metabolites which are putatively acting as mediators of nuclear gene expression. Complimentary, the continuous technological developments in the field of metabolomics per se has further demonstrated its potential as a very suitable readout to unravel metabolite-mediated signalling processes. As foundation for these studies here we review recent advances in elucidating retrograde signalling molecules and pathways with an emphasis on metabolomics and systems biology driven approaches.